Una recepción heterodoxa de Tomás de Aquino de la teoría del alma aristotélica. - Martínez, Jorge (Scripta Mediaevalia, 2024)
In this paper I propose to deal briefly and schematically with two important issues alluded to by Aristotle in the Treatise on the Soul and the interpretation that Thomas Aquinas makes of them in some passages of his work. These two issues are: one, that of the very definition of the soul proposed by Aristotle at the beginning of Book II of De anima and the version that St. Thomas offers of that definition. The other issue is the character of the intellect as part of the soul, and at the same time its character as "separate" from the soul and the compound, that is, from man himself. This latter separation is made manifest at the moment of death, when the only immortal thing that remains is the intellect or mind.